PERLINDUNGAN HUKUM BAGI RAKYAT PENGGUNA TEMPAT USAHA DI PASAR TRADISIONAL DALAM RANGKA MENDAPATKAN SUMBER DANA - Ilman Khairi (Magister Hukum Sekolah Pascasarjana Unida, 2023)
Certificate of Right to Use a Business Place (SHPTU) is proof of ownership of a right to use a business place (stall) in a market owned by market traders. SHPTU has a fairly high economic value. Therefore it is expected that SHPTU can be used as collateral for credit. SHPTU have something in common elements by leasing as in article 1548 of the Civil Code. This study aims to examine how legal protection for users of business premises in traditional markets can be applied and implemented for the ownership of business premises. The research method used in this study is normative juridical research method by adding empirical elements, with qualitative data analysis. Exploring and analyzing data in the form of documents complemented by factual data in the field so that appropriate conclusions can be drawn. The research findings show that SHPTU is not a material right, but considering that SHPTU has economic value and can be transferred. SHPTU of this valuable stall allows it to be used as collateral for credit by referring to the methods contained in Articles 48-49 concerning the Law on Flats by issuing Certificates of Ownership of Buildings and Buildings (SKBG), where the issuance of certificates is the same between Regional Governments in this case Public Works and Housing Services. SKBG is a way out for proof of stall ownership, because the value is very expensive, legal certainty is needed regarding material rights. Keywords: SHPTU; Legal Protection; UMKM.